Thinning effects on forest productivity and site characteristics - Novak, J.; Slodicak, M.; Dusek, D. (Forest Systems, 2011)
A clear-cutting system with soil preparation before replanting is usual for Scots pine stands in many European countries. Additionally, thinning regimes are applied during the rotation. Thus, forest floor is recreated in each rotation and can be influenced by thinning regime. The present study aimed to determine possible effects of thinning on production (evaluated by basal area) and forest-floor status (evaluated by dry mass, carbon and nitrogen content) in pine stands. We used data from four experiments established in 1962 in 25- to 45-year-old pine stands. In 2008, we analysed forest-floor characteristics under the observed stands. The results from basal area evaluation showed different development in treatments on all experiments during and at the end of observation. We observed substantial, but statistically non-significant, differences between treatments in quantity of dry mass (and of carbon and nitrogen) accumulated in humus horizons under Scots pine stands more than 40 years after first thinning.